2020
DOI: 10.3390/w12020546
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of A Rainwater Harvesting System in A Multi-Storey Residential Building in Brazil

Abstract: This article aims to present an economic feasibility and user satisfaction analysis of a rainwater harvesting system in a multi-storey residential building (where there is rainwater to supply toilets) located in Florianópolis, southern Brazil. This research used detailed methods and also considered the opinion and habits of users regarding the use of a rainwater harvesting system. The water end-uses were estimated through questionnaire survey in each flat. The potential for potable water savings was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Many researchers have confirmed that rain harvesting (RH) can provide water in urban/suburban, industrial, and rural areas [107][108][109][110][111][112][113][114][115][116][117][118], promising to save freshwater, a potential that may reduce tensions and competition among users. It is considered a low health risk, cost-efficient, and an environmentally friendly technology [119][120][121], a fact that has allowed its expansion in many developing and developed countries (EU, USA, UK, Japan, South Korea, Australia, and Africa) [116].…”
Section: Use Of Non-conventional Water Resources As a Means To Mitigate Water Competitions And Conflictsmentioning
confidence: 99%
“…Many researchers have confirmed that rain harvesting (RH) can provide water in urban/suburban, industrial, and rural areas [107][108][109][110][111][112][113][114][115][116][117][118], promising to save freshwater, a potential that may reduce tensions and competition among users. It is considered a low health risk, cost-efficient, and an environmentally friendly technology [119][120][121], a fact that has allowed its expansion in many developing and developed countries (EU, USA, UK, Japan, South Korea, Australia, and Africa) [116].…”
Section: Use Of Non-conventional Water Resources As a Means To Mitigate Water Competitions And Conflictsmentioning
confidence: 99%
“…Kuntz and Chisi [28] investigated the economic feasibility and user satisfaction in RWH systems in a residential building in Florianópolis (Brazil) by using a questionnaire survey. The economic feasibility analysis considered different rainwater demands, residents' habits, user satisfaction, and the importance of potable water savings.…”
Section: Rainwater Harvesting (Rwh)mentioning
confidence: 99%
“…Rainwater harvesting is an alternative water supply that can have a significant contribution in meeting future water demands and to maintain/improve the quality of water resources. It has been proven to be a cost-effective solution in urban and sub-urban areas [27,28,[90][91][92][93]. In recent years, there is a growing interest in both developing and developed countries (the EU, the USA, the United Kingdom, Japan, South Korea, Australia, and Africa) for RWH systems [27], driven mainly by their cost efficiency and potential benefits to different sectors of the economy, environment, water resources, and human health [94][95][96].…”
Section: Rainwater Harvestingmentioning
confidence: 99%
“…The sub-surface soil in opening of ridges as showed in Fig. 21 and furrows and plantation of horticulture and forest tree species (Ghisi et al 2007;Kuntz Maykot and Ghisi 2020).…”
Section: Organizational Policies II Government Regulationsmentioning
confidence: 99%